EFFECTS OF SEED MATERIAL AND SOLUTION COMPOSITION ON CALCITE PRECIPITATION - Lin Y.P.; Singer P.C. (My University, 2005)
We studied the effects of seed material and solution composition on calcite crystal precipitation using a pH-stat system. The seed materials investigated included quartz, dolomite, two calcites with different particle size and specific surface area, and two dried precipitates from precipitative softening water treatment plants. Our results indicated that, of the seed materials examined, only calcite had the ability to initiate calcite precipitation in a solution with a degree of supersaturation of 5.3 over a period of two hours, and that the precipitation rate was proportional to the available surface area of the seed. For different solution compositions with the same degree of supersaturation, the calcite precipitation rate increased with increasing carbonate/calcium ratio, which contradicts the generally accepted empirical rate expression that the degree of supersaturation is the sole factor controlling precipitation kinetics. By applying a surface complexation model, the surface concentrations of two species, >CO3− and >CaCO3−, appear to be responsible for catalyzing calcite precipitation.